Use of Biomass Ash in Reinforced Clayey Soil: A Multiscale Analysis of Solid-State Reactions - Maximiliano Fastelli; Costanza Cambi; Azzurra Zucchini; Paola Sassi; Elia Pandolfi Balbi; Leonardo Pioppi; Franco Cotana; Gianluca Cavalaglio; Paola Comodi (Recycling, 2022)
Clayey soils are treated with binding agents to improve their mechanical properties, as these soils are widely used in construction. The production of binding agents is an energy-intensive process and emits significant amounts of CO2. In addition, the interest in recycling industry waste materials has increased, and the management of significant waste from biomass power plants remains an issue. We used three biomass ashes derived from pellet, olive, and grapevine combustion as stabilizing agents of a clayey soil. The mechanical effects of the treatment on clay-ash mixtures were evaluated using confined compressive tests. The mixtures’ chemo-mineralogical evolution was evaluated through X-ray powder diffraction and quantitative Rietveld analysis, Fourier transform infrared spectroscopy (FT-IR), and energy-dispersive X-ray spectroscopy coupled with scanning electron microscopy (EDS-SEM). The FT-IR spectra showed an evolution of the Si-O-Si/Al features, with shifting band positions due to polymerization of the tetrahedral units. The EDS-SEM analysis showed an evolution of the Ca/Si distribution and the growth of pozzolanic reaction products, such as C-S-H nanocrystals and gels. This evidence confirms that the pozzolanic reaction occurs by dissolution of clay minerals and/or the amorphous phase of the ash, which affects the macroscopic behavior of clayey soils in terms of stiffening and strengthening, as confirmed by mechanical tests, albeit these effects are non-homogenous and continuous.